2015
DOI: 10.1111/cid.12350
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Follow‐Up of 2.5‐mm Narrow‐Diameter Implants Supporting a Fixed Prostheses

Abstract: When dental implants of 2.5 mm in diameter are splinted by a fixed prosthesis, long-term favorable outcomes could be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…The measurement of MBLs around NDIs showed a mean value below 1 mm after 5 years since placement, which would indicate the absence of excessive mechanical loading on the 3‐mm‐diameter implants. Similar radiographic results have been reported by Arisan et al 29 and Anitua et al 30 Furthermore, NDIs were associated with a similar bone loss at 5 years compared with SDIs. This result seems to contradict findings of previous experimental studies using finite element analyses, in which implant diameter reduction was associated with a greater stress and strain concentration around the head of the implants 14 , 31 .…”
Section: Discussionsupporting
confidence: 88%
“…The measurement of MBLs around NDIs showed a mean value below 1 mm after 5 years since placement, which would indicate the absence of excessive mechanical loading on the 3‐mm‐diameter implants. Similar radiographic results have been reported by Arisan et al 29 and Anitua et al 30 Furthermore, NDIs were associated with a similar bone loss at 5 years compared with SDIs. This result seems to contradict findings of previous experimental studies using finite element analyses, in which implant diameter reduction was associated with a greater stress and strain concentration around the head of the implants 14 , 31 .…”
Section: Discussionsupporting
confidence: 88%
“…() concluded that small‐diameter implants could be successfully used as low‐cost solution; however, higher failure rates were reported with shorter and narrow implants. Some studies have suggested that the length has a direct impact on implant survival rate, considering that longer implants are able to better disperse the occlusal forces and reach better implant stability; however, this is still a controversial topic (Anitua, Saracho, Begoña, & Alkhraisat, ; Ortega‐Oller et al., ; Sohrabi et al.,).…”
Section: Discussionmentioning
confidence: 99%
“…), prosthesis design (Anitua et al. ), bone quality, soft tissue‐related factors, smoking and oral hygiene habits, age and gender (Negri et al. ), bone quantity, final drill during implant placement, healing time before prosthesis delivery (Galindo‐Moreno et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, factors that influence peri-implant bone loss at early stages are of great importance. The available literature has shown a key role of implant diameter, length and depth with respect to the bone crest (Liaje et al 2012;Zweers et al 2015), prosthesis design (Anitua et al 2015), bone quality, soft tissue-related factors, smoking and oral hygiene habits, age and gender (Negri et al 2014), bone quantity, final drill during implant placement, healing time before prosthesis delivery (Galindo-Moreno et al 2012) as well as platform-switching (Canullo et al 2010(Canullo et al , 2011(Canullo et al , 2012 and prosthesis abutment height , 2016 and connection design (Galindo-Moreno et al 2015a). A summary of this evidence shows that narrow-diameter implants that are placed below the crestal bone in patients who smoke, with under-preparation of the implant bed and restored with individually cemented crowns soon after they are placed, are more likely to lose more marginal bone in the early stages.…”
Section: Discussionmentioning
confidence: 99%